The captive imagination : addiction, reality, and our search for meaning - Dakwar, Elias (Harper, and imprint of HarperCollins Publishers, 2024)
"Addiction has been called a moral failing, a social problem, a spiritual crisis, a behavioral disorder, and a brain disease. It has also been called a class issue, a supply problem, a problem of learning, a memory disorder, and a result of trauma. And some propose that addiction is neither a disease nor a problem, but a transgressive expression of freedom, a maligned sub-culture, a therapeutic relationship. Even the term 'addiction' is open to question. There are few human phenomena so elusive and intractable; after decades of neuroscientific research, we aren't much closer to understanding addiction, nor to addressing it effectively. This profusion of interpretations, meanings, and models reflects a hidden truth about addiction: that it is profusely generative of meaning itself. In this bold reimagining, pioneering psychiatrist Elias Dakwar examines addiction as a sustained creative act--and specifically as a process of personal world-building, complete with its own rituals, systems of value, modes of suffering, and sources of support. In this regard, addiction is something we all do. But there is a crucial difference. In the case of those of us suffering from addiction explicitly, this meaningful world keeps us in clear captivity, worsening the suffering and confusion we hoped it would console. And we remain stuck because we have trouble imagining it differently. Drawing on vivid stories of his own patients, path-breaking research with meditation, psychotherapy, and psychedelics/hallucinogens, and decades of clinical experience, Dakwar explores this captivity at the heart of our addictions, and shows how we might move beyond its bounds to reclaim our freedom. He also relates addiction to our collective self-inflicted crises, from environmental destruction to militarism to social injustice, rendering this often stigmatized condition relevant to all of us. With fluid, rich, and often startling prose, The Captive Imagination offers a novel path for better understanding and overcoming addiction, as well as human suffering more generally"--